2017
DOI: 10.1007/s10067-017-3897-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between leptin and IL-6 concentrations with cardiovascular risk in patients with rheumatoid arthritis

Abstract: Pro-inflammatory cytokines such as leptin and IL-6 play an important role in the development of cardiovascular risk. Determine the relationship between leptin and IL-6 concentrations with cardiovascular risk in patients with rheumatoid arthritis. We determined IL-6 and leptin levels in 77 patients with the diagnosis of rheumatoid arthritis. The cardiovascular risk was calculated using the modified Framingham scale. Statistical analysis was performed using SPSS 22 considering a significant p < 0.05. Serum lepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Cardiovascular risk is another factor associated to obesity and RA pathology. Accordingly, Batun et al reported an association between leptin and IL-6 concentrations with cardiovascular risk in these patients [124].…”
Section: Leptinmentioning
confidence: 99%
“…Cardiovascular risk is another factor associated to obesity and RA pathology. Accordingly, Batun et al reported an association between leptin and IL-6 concentrations with cardiovascular risk in these patients [124].…”
Section: Leptinmentioning
confidence: 99%
“…This observation may be supported that it may inhibit cytosolic insulin metabolizing enzymes and minimize its degradation [24]. In the same line, other studies document the beneficial impact of HCQ in correction of different adipokines levels such as leptin, adiponectin, and significant reduction of the vascular endothelial stress markers such as sICAM and sVICAM [25], [26].…”
Section: Discussionmentioning
confidence: 72%
“…Another study yielded similar results with SLE patients treated with HCQ finding that the concentrations of IL-6, IL-1β and TNF-α were elevated prior to treatment, and reduced after two months of treatment (Monzavi et al 2018). Several additional studies have demonstrated that HCQ decreases elevated IL-6 concentrations in RA and SLE patients (da Silva et al 2013;Batún-Garrido et al 2018) and in an animal model of neuroinflammation (Koch et al 2015). Similarly, studies testing the antiviral activity of HCQ for the treatment of HIV showed that the drug reduced HIV RNA copy number and decreased IL-6 concentrations (Sperber et al 1995).…”
Section: Approved Mediations That Reduce Cytokines Involved In the Csmentioning
confidence: 73%